Pengaruh Kesadaran Membayar Pajak, Pemahaman Tentang Perpajakan Dan Persepsi Atas Efektifitas Sistem Perpajakan Terhadap Kemauan Membayar Pajak Pada Wajib Pajak Orang Pribadi Di Kota Langsa - Dinda Khairina; Tuti Meutia; Yani Rizal (Ekonomi Bisnis Manajemen dan Akuntansi (EBMA), 2023)
This study aims to determine the influence of awareness of paying taxes, understanding of taxation, perceptions of the effectiveness of the tax system on the willingness to pay taxes on individual taxpayers in Langsa. The population is taxpayers from non-employee, and the sample is 100 people with the sampling technique using Random Sampling. The method used is a quantitative method. The data collection method uses a questionnaire using a measuring instrument in form of a validity test and a reliability test. The data analysis method used is multiple linear regression, t test, F test, and coefficient of determination test. The equation for the results of the regression analysis Y = 11.356 + 0.546 X1 + 0.448 X2 + 1.240 X3 + e. The results of the t-test for the variable awareness of paying taxes (X1) are 2,180 with a t-sig of 0,040, the variable understanding of taxation (X2), results are 2,175 with a t-sig of 0,034. sig 0.036. The results of the F test obtained a significance result of 0.000, and a coefficient of determination test result of 41.9%. So the conclusion is that the variables of awareness of paying taxes, understanding of taxation, perceptions of the effectiveness of the taxation system have a positive and significant simultaneous effect on the willingness to pay taxes in Langsa City.